Education for Sustainable Development in Chile: A Pedagogical Deconstruction for an Active Citizenship - Berríos Villarroel, Adolfo (2020)
The present essay analyses the outlook of the education for sustainable development in Chile. For that aim, we examine different proposals from international organizations, and, in turn, how these proposals have been adapted and introduced into the Chilean educational system. The epistemological fundaments that support these “eco-educational” politics are put in tension on this text, inviting to deconstruct the foundation of the sustainable development model, and its limitations to the practice of an active citizenship in the local context. In order to accomplish this reflection, the article firstly expounds on the primary landmarks of sustainable development in the educational subject, facing the concept of citizenship that this programme proposes, with the concept of citizenship displayed in the main landmarks of political thinking. Secondly, the analysis delivers a proposal regarding the tools given by critical pedagogy, in order to expose the complexity involved when dealing with the sustainable development model in the classroom. For this purpose, we base upon Paulo Freire’s critical pedagogy’s approach. As a final reflection, a pedagogical perspective is proposed, which allows a transformation of the instrumental nature given to future citizens by current educational activities, with the aim of developing an active citizenship from a collective and local perspective. Finally, the text prompts the question about the extent in which the early training of future Chilean teachers contributes to develop the necessary pedagogical competences, in order to examine and enrich the civic recommendations proposed in the educational programmes regarding sustainable development.